Climate change, geography and trade agreements: A perspective of Asian bilateral trade - Qianxu Liang; Lin Shao; Zahid Hussain; Yufang Chao; Haiying Liu; Chaonan Wang (PLoS ONE, 2025)
This study investigates the simultaneous effects of geographic factors, trade agreements, and climate change on bilateral exports in Asian countries. We estimate the correlation with bilateral exports by utilizing a panel data set from 2000 to 2020, employing various econometric techniques, particularly the structural gravity model. Therefore, this study aims to examine the simultaneous or complementary impact of influencing factors on exports and link them with the gross domestic product. Findings demonstrate that geographic factors are crucial for determining bilateral exports in terms of increasing trends. Furthermore, geography plays a crucial role in enhancing the magnitude and probability of bilateral exports between trading partner countries. Moreover, bilateral exports have declined because of the simultaneous impact of geographic factors, climate change, and economic size. Thus, geographic factors and economic size affect marginal exports to varying degrees. This study suggests that the simultaneous increase in economic size, trade agreements, and geographic factors can enhance the bilateral export level and its probability at an above-average rate between trading partner countries.